PERLINDUNGAN HUKUM TERHADAP HAK ATAS LINGKUNGAN HIDUP DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL DAN HUKUM NASIONAL INDONESIA - Richard Waas (SASI, 2014)
This writing background by the environmental degradation that affect humans, so that the right to a good environment and healthy to be neglected. Thus, the issue raised is: How Legal Protection Against Environmental Rights Seen from the Perspective of International Law and National Law Indonesia. Human life and the environment is an integral part, like two sides of a coin are related to each other. The environment is good and healthy, it would be good also for the man himself. Environmental conditions in the world, including Indonesia, have been degraded or decline in environmental quality. This, as a result of human actions by destroying and polluting the environment that have an adverse impact on other human beings. Damage and environmental pollution, will have an impact on the right to good environment and healthy. When the environment becomes good or damaged, it will disturb the social order it self